Analyzing students’ learning strategies using item response theory: Toward assessment and instruction for self-regulated learning - Uesaka, Yuri; Suzuki, Masayuki; Ichikawa, Shin’ichi (Frontiers in Education, 2022)
Many previous studies related to self-regulated learning have demonstrated that students with higher academic achievement tend to use varied and effective learning strategies. However, they cannot acquire these strategies in a short period. If learning strategies are acquired and used gradually, it may help specify individual levels of use and teach its usage in a reasonable order. Therefore, this study analyzed data on strategy use with item response theory (IRT) to specify students’ level of strategy acquisition and determine how they are ordered. Questionnaire data on the frequency of learning strategy use were obtained from students in five universities (N = 472) and analyzed using a IRT model. It was shown that the average levels of students’ strategy acquisition were related to their universities’ academic achievement rankings.